Developing Virtual Herbarium of Sunan Kalijaga Islamic State University as a Plant Taxonomy Complementary Lab Work Material - Muhammad Ja'far Luthfi; Riyanto Riyanto; Widodo Widodo (Biology, Medicine, & Natural Product Chemistry, 2023)
This research combines the fields of biology, photography, graphic design, and informatics. This study aims to develop a virtual herbarium museum through website media. The research was done to improve the accessibility and sharing of data (free access) herbarium. Website development was performed using the SDLC (Systems Development Life Cycle) which consists of 5 (five) steps, namely planning a strategic website development plan, determining the scope of development, analyzing the required needs, designing and implementing website creation and testing. Based on the results of system testing and implementation, it can be concluded that the virtual herbarium museum has been successfully built as a plant taxonomy complementary lab work material.